Comprehensive Histopathological Properties of Dartos Tissue Associated with Hypospadias Severity and Chordee: A Prospective Study - Raharja, Putu Angga Risky; Birowo, Ponco; Rachmadi, Lisnawati; Wibowo, Heri; Kekalih, Aria; Duarsa, Gede Wirya Kusuma; Wahyudi, Irfan (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2024)
Background: The cause of chordee in hypospadias is not fully understood. Dartos fascia resection has been shown to correct penile curvature, suggesting its potential involvement. This study aimed to evaluate the histopathological properties of dartos tissue and their association with hypospadias severity and chordee.Methods and Materials: Dartos tissue samples were collected from 37 children with hypospadias and ten controls undergoing circumcision between March and October 2024. Histopathological analysis using hematoxylin-eosin and Masson’s trichrome staining assessed for collagen, smooth muscle, and vascular density. Assessment and quantification of all histopathological components were blinded. Results: The hypospadias group showed lower collagen density (60.85±6.75% vs. 67.31±4.61%; p=0.003) and higher smooth muscle density (7.34±4.92% vs. 2.51±2.24%; p<0.001) compared to controls, with no significant difference in vessel density. Sub-analysis showed severe chordee was linked to lower collagen density compared to mild (Mean Difference [MD] -6.24±2.41%; p=0.014) and moderate chordee (MD -5.73±2.54%; p=0.031). Conclusions: The dartos tissue in hypospadias patients exhibited lower collagen density and higher smooth muscle density, with chordee severity specifically linked to decreased collagen density.